2017
DOI: 10.3238/arztebl.2017.0653
|View full text |Cite
|
Sign up to set email alerts
|

The Health Effects of Aluminum Exposure

Abstract: The internal aluminum load is measured in terms of the concentration of aluminum in urine and blood. Keeping these concentrations below the tolerance values prevents the development of manifest and subclinical signs of aluminum toxicity. Large-scale epidemiologic studies of the relationship between aluminum-containing antiperspirants and the risk of breast cancer would be desirable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
161
1
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(170 citation statements)
references
References 51 publications
2
161
1
6
Order By: Relevance
“…Exposure to intolerable levels of Al may be a source of respiratory and neurological disorders. Studies have confirmed that this metal, Al is partly responsible for brain loss and a source of diseases such as Parkinson's disease, anemia, dementia, blood and dental problems [71]. In this study Al concentration ranged from 561-942 mg/kg in soils, and 23-286 mg/kg in vegetables.…”
Section: Aluminumsupporting
confidence: 58%
“…Exposure to intolerable levels of Al may be a source of respiratory and neurological disorders. Studies have confirmed that this metal, Al is partly responsible for brain loss and a source of diseases such as Parkinson's disease, anemia, dementia, blood and dental problems [71]. In this study Al concentration ranged from 561-942 mg/kg in soils, and 23-286 mg/kg in vegetables.…”
Section: Aluminumsupporting
confidence: 58%
“…Vaccine adjuvants may contribute to antigen delivery and/or enhancing an immune response. 5,6 In addition, alum, oil-in-water emulsions (such as incomplete Freund's adjuvant [IFA]) and MPLA have long been associated with inflammation. 4 It is known that alum does not induce a cellmediated immune response that can effectively clear intracellular pathogens.…”
Section: Introductionmentioning
confidence: 99%
“…4 It is known that alum does not induce a cellmediated immune response that can effectively clear intracellular pathogens. 5,6 In addition, alum, oil-in-water emulsions (such as incomplete Freund's adjuvant [IFA]) and MPLA have long been associated with inflammation. 7,8 Amphiphilic block copolymers consisting of polyoxypropylene and polyoxyethylene blocks, including the widely used surfactant Pluronic F127 that has been approved by the FDA for other applications, 9 have been evaluated as injectable drug and vaccine delivery systems with tunable release rates based on polymer concentration.…”
Section: Introductionmentioning
confidence: 99%
“…Although Ni has biological activity in bacteria at nanomolar concentrations [17][18][19], it is also considered as a highly toxic metal [20], by the aim of causing the elevated production of reactive oxygen species and DNA damage [21]. In the case of Al, its embryotoxic effects in animal models and its neurotoxic effects in humans have been demonstrated, suggesting that this metal exposition may cause specifi c encephalopathy with a dementia syndrome [22].…”
Section: Introductionmentioning
confidence: 99%